Maternal preconception body mass index and offspring cord blood DNA methylation: Exploration of early life origins of disease. (15th November 2013) - Liu, Xin; Chen, Qi; Tsai, Hui‐Ju; Wang, Guoying; Hong, Xiumei; Zhou, Ying; Zhang, Chunling; Liu, Chunyu; Liu, Rong; Wang, Hongjian; Zhang, Shanchun; Yu, Yunxian; et al.
<x xml:space="preserve">Abstract</x> Maternal obesity is associated with a variety of common diseases in the offspring. One possible underlying mechanism could be maternal obesity induced alterations in DNA methylation. However, this hypothesis is yet to be tested. We performed epigenomic mapping of cord blood among 308 Black mother‐infant pairs delivered at term at the Boston Medical Center using the Illumina HumanMethylation27 BeadChip. Linear regression and pathway analyses were conducted to evaluate the associations between DNA methylation levels and prepregnancy maternal BMI (<25, 25–30, ≥30 kg/m2). The methylation levels of 20 CpG sites were associated with maternal BMI at a significance level of P‐value <10−4 in the overall sample, and boys and girls, separately. One CpG site remained statistically significant after correction for multiple comparisons (FDR corrected P‐value = 0.04) and was annotated to a potential cancer gene, ZCCHC10. Some of the other CpG site annotated genes appear to be critical to the development of cancers and cardiovascular diseases (i.e., WNT16, C18orf8, ANGPTL2, SAPCD2, ADCY3, PRR16, ERBB2, DOK2, PLAC1). Significant findings from pathway analysis, such as infectious and inflammatory and lipid metabolism pathways, lends support for the potential impact of maternal BMI on the above stated disorders. This study demonstrates that prepregnancy maternal BMI might lead to alterations in offspring DNA methylation in genes relevant to the development of a range of complex chronic diseases, providing evidence of trans‐generational influence on disease susceptibility via epigenetic mechanism. Environ. Mol. Mutagen. 55:223–230, 2014. © 2013 Wiley Periodicals, Inc.